Challenges in diagnosis and treatment of scleroderma renal crisis (clinical case report) - E. M. Mishina; E. M. Mishina; M. D. Evsikova; O. A. Koneva (Современная ревматология)
The pathogenesis and diagnostic approaches to scleroderma renal crisis (SRC) – an acute “scleroderma kidney” – a severe and life-threatening complication of systemic sclerosis (SSc) characterized by high mortality, are discussed. Due to limited understanding of the underlying pathogenic mechanisms, a standardized treatment for SRC has not been developed.We describe the development of acute SRC in a 43-year-old female patient with diffuse form of SSc of 1.5 years’ duration, rapidly progressive disease course, and internal organ involvement associated with high immunological activity. This case is notable in that the renal crisis developed during hospitalization and was observed from the earliest days under well-documented therapy. The treatment involved the use of several agents with different mechanisms of action, including rituximab, mycophenolate mofetil, a phosphodiesterase-5 inhibitor (sildenafil), and courses of prostanoids. The glucocorticoid dose remained low (methylprednisolone 8 mg/day). Complete resolution of SRC was achieved with restoration of renal function.